Rekonstruksi Batas Diskresi Fiskal Pemerintah dalam Keadaan Darurat Berdasarkan Prinsip Proposionalitas Konstitusional - Evita Isretno Israhadi; Ariffianto Wibi Wibowo; Henny Yuliyanah; Muhlis Muhlis; Yelris Gabetua (Jurnal Ragam Pengabdian, 2026)
Government fiscal discretion during emergencies is essential for ensuring effective governance in responding to economic crises, pandemics, and national disasters. However, the current legal framework emphasizes governmental authority rather than its limitations, creating legal uncertainty and failing to fully reflect the principle of constitutional proportionality. This study aims to examine why the existing limits on fiscal discretion do not embody constitutional proportionality and to propose a reconstruction based on this principle. Using a normative legal method with statutory and conceptual approaches, the study analyzes primary, secondary, and tertiary legal materials through qualitative legal interpretation and argumentation. The findings reveal ambiguous legal norms regarding the scope of fiscal authority, the absence of proportionality parameters as standards for exercising discretion, and weak constitutional oversight mechanisms. The proposed reconstruction establishes constitutional proportionality as the foundation for regulating fiscal discretion by defining clear limits on governmental authority, strengthening oversight, and restricting the scope and duration of emergency fiscal measures. This reconstruction is expected to improve legal certainty, accountability, and constitutional control over state financial management during emergency situations.